Critical Early Roles for col27a1a and col27a1b in Zebrafish Notochord Morphogenesis, Vertebral Mineralization and Post-embryonic Axial Growth - Christiansen, Helena E.; Lang, Michael R.; Pace, James M.; Parichy, David M. (PLOS ONE, 2010)
Background Fibrillar collagens are well known for their links to human diseases, with which all have been associated except for the two most recently identified fibrillar collagens, type XXIV collagen and type XXVII collagen. To assess functions and potential disease phenotypes of type XXVII collagen, we examined its roles in zebrafish embryonic and post-embryonic development. Methodology/Principal Findings We identified two type XXVII collagen genes in zebrafish, col27a1a and col27a1b. Both col27a1a and col27a1b were expressed in notochord and cartilage in the embryo and early larva. To determine sites of type XXVII collagen function, col27a1a and col27a1b were knocked down using morpholino antisense oligonucleotides. Knockdown of col27a1a singly or in conjunction with col27a1b resulted in curvature of the notochord at early stages and formation of scoliotic curves as well as dysmorphic vertebrae at later stages. These defects were accompanied by abnormal distributions of cells and protein localization in the notochord, as visualized by transmission electron microscopy, as well as delayed vertebral mineralization as detected histologically. Conclusions/Significance Together, our findings indicate a key role for type XXVII collagen in notochord morphogenesis and axial skeletogenesis and suggest a possible human disease phenotype.